(untitled) (Herald of Journalism, 2026)
The rapid development of motion news highlights the necessity of exploring spatial transformations in news communication, particularly the evolution from two-dimensional news visualization to three-dimensional spatial immersion. While existing research has examined narrative strategies and visual presentation in motion news, its role in reconstructing digital news media spaces remains understudied. Audience perceptions and interaction patterns with spatial motion news may influence immersion and communication effectiveness, yet these spatial perception mechanisms have received little in-depth exploration. This study aims to investigate how motion news reconstructs digital news media spaces through spatial immersion and analyzes the impact of three-dimensional motion news on user immersion, information retention, and perceptions of news authenticity. Employing quantitative research methods with The Beijing News’ three-dimensional motion news as the sample, combined with user experiments, this study comprehensively examines the logic of motion news in reconstructing news communication spaces. Findings indicate that the three-dimensional spatial construction of motion news significantly enhances audience immersion and information comprehension while altering users’ judgment logic regarding news authenticity. The study concludes that integrating spatial immersive narratives into motion news effectively enhances digital news dissemination outcomes and promotes a multidimensional understanding of news events. These findings provide practical pathways for advancing “Generative Spatial News,” highlighting the immense potential of spatial journalism in elevating communication effectiveness and user cognitive experiences.